Domestic hot water usage measurement with one minute resolution for 648 apartments in Swedish multi-family buildings - Eklund, Petter; Averfalk, Helge (Halmstad University, 2025)
A time-series of domestic hot water usage for 648 individual apartments in eight separate multi-family buildings of different sizes and located in multiple Swedish towns. The measurements were performed in February and March of 2021. The values recorded are cumulative usage in liters with a time resolution of 1 minute. The length of the time-series is either 22 days or 25 days depending on which of the buildings in the study the apartment belongs to.

En tidsserie av varmvattenförbrukning för 648 individuella lägenheter i åtta separata flerfamiljshus av olika storlekar belägna i flera svenska städer. Mätningarna utfördes i februari och mars 2021. De registrerade värdena är kumulativ förbrukning i liter med en tidsupplösning på 1 minut. Tidsseriens längd är antingen 22 dagar eller 25 dagar beroende på vilken av byggnaderna i studien lägenheten tillhör.
Mätning av varmvattenförbrukning med en minuts upplösning för 648 lägenheter i svenska flerfamiljshus
Keywords: water-meters; vattenmätare; drinking water; dricksvatten; water use; vattenanvändning; household water; hushållsvatten; water supply; vattenförsörjning; water services; vattentjänster; tap water; kranvatten; water consumption; Domestic hot water; Tappvarmvatten; Energy Engineering; Energiteknik